Perceptions and practices on malaria in a rural population of Koraput district, Odisha - Padhan, Prakash; Bindhani, Basanta Kumar; Nayak, Jayanta Kumar (International Journal of Research in Medical Sciences, 2021)
Background: Malaria is a mosquito-borne disease caused by a protozoan parasite i.e. Plasmodium parasites. It is one of the most prevalent disorders worldwide. India ranked the fourth-highest number of death cases. In Odisha, more than two-thirds of malaria cases are reported from ten southern districts. A high risk of malaria infection is found in Koraput district of Odisha. The present study aims to access the knowledge, attitude, and practices (KAP) about malaria among the individuals of Koraput district, Odisha. Methods: This is a cross-sectional study and 258 respondents were taken randomly from five villages of Koraput district. Data on demographics as well as knowledge, attitude, and practices about malaria was collected by using self-modified and pretested schedules. Results: A significant number of the respondent (97.29%) have reported that they had heard about malaria. 37.60% of respondents answered that they knew it from television, followed by health workers (23.26%) and friends (20.54%). The majority (98.06%) of the sample reported that it is caused by mosquito bites. Almost 63% of the respondents were consulted with a doctor whereas 24.81% consulted first to traditional healers of that region. The majority (99.22%) has a mosquito net and 98.83% of them were used it after a proper wash. Conclusions: Although the study found good knowledge on malaria, still further awareness is required to elevate the present status. In this study most of the respondents had a good level of knowledge about malaria, however, attitude and practices about malaria prevention still need to be improved.